GERAKAN SOSIAL PEMBERDAYAAN SENTRA TERNAK DOMPET DHUAFA WASPADA DI DESA BULU CINA KABUPATEN DELI SERDANG - Harahap, Mulia Wilandra; Riza, Faisal; Desky, Ahmad Fernanda (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
This study seeks to describe the Social Movements carried out by Dompet Dhuafa Waspada with its Livestock Center program in Bulu Cina Village, Deli Serdang Regency. The social movement carried out by Dompet Dhuafa Waspada then resulted in an empowerment aimed at the underprivileged community. In this study, the point of view used by researchers is based on the theory of Social Movements initiated by Charles Tilly. The method used in this study is a qualitative research method by observing, documenting and direct interviews to data sources. It can be identified that the social movement carried out by Dompet Dhuafa Waspada is a collective social movement. As Tilly said, that there is a necessity for change to occur which encourages collective action to create a movement.